Every person has a history - Vickers, Rebecca (Chicago, Ill Heinemann Library, 2014)
From important historical figures and inventors of everyday products, to the people behind the names of local road signs - we are surrounded by traces of individuals whose history we can research. Even a person who is not well known might have had a surprising life - but how do we find this out? Using examples, from famous figures such as Usain Bolt and Winston Churchill, to those with less familiar stories
A gift from book Africa
Famoius People
Hardcover
1 2 13
Keywords: Biography -- Research -- Methodology -- Juvenile literature; Biography as a literary form -- Juvenile literature; Research -- Juvenile literature